Insect and Mite Management Suggestions for Commercial Poinsettia Production - James F. Price; Curtis Nagle; Elzie McCord, Jr. (EDIS, 2009)
Revised! ENY-307, a 96-page guide by James F. Price, Curtis Nagle, and Elzie McCord, Jr., aids in the selection of insect and mite control measures for commercial producers of this flower that is synonymous with Christmas. Published by the UF Department of Entomology and Nematology, December 2008.